INFLUENCE OF WORK-FAMILY CONFLICT, FAMILY-WORK CONFLICT AND WORK STRESS ON THE PERFORMANCE OF FEMALE TEACHERS IN-STATE HIGH SCHOOL GROUP 05 TANGERANG DISTRICT OF BANTEN PROVINCE - Sutihat, Ihat; Chaerudin, Chaerudin (Dinasti Publisher, 2021)
The main problem in this research was the discovery of work-family conflicts, family-work conflicts, and work stress on female teachers in The State High School Cluster 05 Tangerang Regency of Banten Province, which is an indication-based on the low performance of the teacher. This study uses descriptive methods with quantitative approaches, and those subjects are all female teachers in cluster 05 with a total of 150 people, and the sample turns into 60 female teacher respondents who have a family. The analysis method is multiple linear regression analysis, to obtain valid and reliable data so the results can be used to understand and anticipate problems in school organizations. The results partially showed that work-family conflict, family-work conflict, and work stress did not significantly affect the performance of female teachers, but still had an impact on the performance of female teachers of Cluster 05 High School in Tangerang Regency, Banten Province. Therefore, female teachers should be able to balance professionalism as a teacher by exploring performance competencies in female teachers, both in innovative and creative teaching initiatives, and building good communication in the family to create family harmony that can support a woman's career, and reduce the work stress with all ambiguities due to her dual role.